PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Da'a, Fitrianti; Suwarni, Wa Ode; Iqram, Muhamad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This research aims to analyze the influence of liquidity, profitability and leverage on stock returns in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This type of research is quantitative descriptive with data collection techniques using documentation methods. This research uses a purposive sampling technique. The population in this study was 11 companies and 9 companies passed the criteria. The data analysis technique used in this research is multiple linear regression. The research results show that liquidity, profitability and leverage simultaneously have no effect on stock returns. The results of the t test show that partial liquidity has no effect on stock returns, partial profitability has no effect on stock returns and partial leverage has no effect on returns.